When I say…response process validity evidence. Issue 9 (15th June 2022) - Shankar, Sneha; St‐Onge, Christina; Young, Meredith E.
Abstract : In the latest "When I Say..." response process validity evidence is argued as requiring emotional and motivational processes, in addition to cognitive, if we are to strive for equity and fairness in educational measurement.